Glutathione sensitive vesicles prepared from supramolecular amphiphiles. Issue 42 (11th October 2021) - Mobley, Emily B.; Byrd, Natalie; Yim, Matthew G.; Gariepy, Rachel; Rieder, Maya; Ward, Sandra
Abstract : Novel glutathione sensitive vesicle nanocarriers formed from supramolecular amphiphiles degrade via a thiol–disulfide exchange at the vesicle surface. Abstract : Glutathione (GSH) sensitive vesicles were prepared by the self-assembly of amphiphilic inclusion complexes. These novel chemically sensitive supramolecular amphiphiles are anticipated to have applications in drug delivery; the nanocarriers can protect the encapsulated cargo and release it via triggered degradation in high concentrations of GSH. Additionally, the sensitivity of the vesicles to GSH indicates that the dynamic covalent disulfide bond at the vesicle surface can be used for post-modification of the nanocarrier via a thiol–disulfide exchange, a strategy that can be exploited to introduce targeting moieties to increase treatment specificity. Supramolecular amphiphiles containing a dynamic covalent disulfide bond were prepared via the host–guest inclusion complexes between alkylated β-cyclodextrin (β-CD) hosts and adamantane terminated polyethylene glycol derivatives. The significant difference between the critical micelle concentrations of the supramolecular amphiphiles and the individual host and guest components confirmed that a unique supramolecular amphiphile was formed. Fluorescence experiments and dynamic light scattering (DLS) revealed that the supramolecular amphiphiles self-assembled into vesicles of 130 nm diameter which were stable for 8 months. Degradation of the vesicles after incubation with GSH was monitored using DLS and by the release of encapsulated 5, 6-carboxyfluorescein (CF), observed by an increase in fluorescence intensity. Degradation of the nanocarrier was faster at intracellular GSH concentrations than at extracellular GSH concentrations.